PENINGKATAN KEMAMPUAN PENALARAN MATEMATIKA SISWA MELALUI MODEL PROBLEM BASED INSTRUCTIONAL (PBI) - Rieke Alyusfitri (PAKAR Pendidikan, 2017)
Learning mathematics at school mostly involving mathematical reasoning abilities. Weakness in the reasoning of students in mathematics learning visible from students' mistakes in solving math problems.Efforts should be made to improve the ability of students' mathematical reasoning can be through the model Problem Based Instrutional (PBI).Problem Based Instructional a learning that begins with the presentation of an authentic and meaningful issues that the students will be able to conduct investigations and menutut solving by the students themselves.So with the model Problem Based Instructional able to assist students in improving students' mathematical reasoning abilities.